Abundance of sedentary consumers and sessile organisms along the wave exposure gradient of subtropical rocky shores of the south-west Atlantic - Christofoletti, Ronaldo A.; Takahashi, Camila K. [UNESP]; Oliveira, Diogo N. [UNESP]; Flores, Augusto A. V. (Cambridge University Press, 2011)
Sedentary consumers play an important role on populations of prey and, hence, their patterns of abundance, distribution and coexistence on shores are important to evaluate their potential influence on ecosystem dynamics. Here, we aimed to describe their spatio-temporal distribution and abundance in relation to wave exposure in the intertidal rocky shores of the south-west Atlantic to provide a basis for further understanding of ecological processes in this system. The abundance and composition of the functional groups of sessile organisms and sedentary consumers were taken by sampling the intertidal of sheltered and moderately exposed shores during a period of one year. The sublittoral fringe of sheltered areas was dominated by macroalgae, while the low midlittoral was dominated by bare rock and barnacles. In contrast, filter-feeding animals prevailed at exposed shores, probably explaining the higher abundance of the predator Stramonita haemastoma at these locations. Limpets were more abundant at the midlittoral zone of all shores while sea urchins were exclusively found at the sublittoral fringe of moderately exposed shores, therefore, adding grazing pressure on these areas. The results showed patterns of coexistence, distribution and abundance of those organisms in this subtropical area, presumably as a result of wave action, competition and prey availability. It also brought insights on the influence of top-down and bottom-up processes in this area.
Keywords: rocky shores; whelks; limpets; sea urchins; distribution; wave exposure; macroalgae; filter-feeding animals